Le plateau de Mondeville (Calvados) Du Néolothique à l'âge du Bronze - Chancerel, Antoine; Marcigny, Cyril; Ghesquière, Emmanuel (Documents d'archéologie française, 2006)
In the 1980s and early 1990s, the municipalities of Mondeville, Grentheville, Cormelles-le-Royal and Giberville in the Calvados area of Normandy were the focus for a vast campaign of "préventive" (rescue) archeology. A few years after the close of the excavations, a considerable body of findings has amassed. By allowing us to consider areas several hundred hectares in extent, the research presented in the present volume paves the way for a full-scale approach to territorial archeology, from the emergence of the first farming communities to the metalworkers of the Late Bronze Age and Early Iron Age - a period of almost 5,000 years. We can observe the inhabitants settling, evolving slowly and progressively shaping the occupation of the plateau. By highlighting the relationships between Normandy and Brittany, the Paris Basin and the British Isles, the study enhances our understanding of the development and diffusion of the various regional cultures and sheds light on the pre- and protohistory of this part of the Caen Plain.